Antimicrobial Activity of Extract and Fractions of Different Parts and GC-MS Profiling of Essential Oil of Cichorium intybus Extracted by Super Critical Fluid Extraction - Afzal1, Muhammad; Shahid1, Muhammad; Mehmood1, Zahid; Anwer Bukhari2, Shazia; Munsif Ali Talpur3, Mir (Asian Journal of Chemistry, 2014)
Present study was conducted to appraise the antimicrobial potential of organic extracts of different parts of plant. Cichorium intybus widely known for their antimicrobial potential was used in the present investigation. Dry root, stem and leaves of medicinal plant was grounded to fine powder and extracted in methanol for 20 days. After this, methanol was allowed to evaporate and resulting residue was dissolved in different sequential solvents viz., hexane, ethyl acetate, n-butanol and water. Fraction of different organic solvents were used for antimicrobial activity. Essential oil of whole plant was extracted using supercritical fluid extraction method. Chemical profiling of essential oil was determined using GC-MS analysis. It is evident from the results of GC-MS analysis that essential oil of medicinal plant contains biological active organic compounds. Essential oil was also used against different bacterial and fungal strains that exhibited conspicuous antimicrobial activity. selected microorganisms Aspergillus niger, Fusarium solnai, Staphylococcus aureus and Escherichia coli were tested with activity (20 ± 1, 20 ± 0.6, 22 ± 0.4 and 24 ± 0.2, respectively). Major constituents of essential oil determined by GC-MS analysis were tetratriacontane (21.58 %), tetracosane (11.27 %), hexatriacontane (10.19 %), 9-octadecenoic acid, 1,2,3-propanetriyl ester, (E,E,E)- (8.02 %) and heneicosane (7.03 %). Antimicrobial potential of essential oil could have been due to these major constituents.